Gene expression network regulated by DNA methylation and microRNA during microcystin-leucine arginine induced malignant transformation in human hepatocyte L02 cells. (1st June 2018) - Chen, Hong-qiang; Zhao, Ji; Li, Yan; He, Li-xiong; Huang, Yu-jing; Shu, Wei-qun; Cao, Jia; Liu, Wen-bin; Liu, Jin-yi
Highlights: A group of key genes and microRNAs significantly changed in the malignant transformation of L02 cells induced by MC-LR. There are 2592 CpG sites differentially methylated in promoter or CDS of genes identified in MC-LR treated L02 cells. DNMT3a and DNMT3b were dramatically up-regulated. MYLK3, EGFR and ZNF704, which simultaneously regulated by microRNA and DNA methylation, affect the cell cycle and apoptosis. Abstract: Microcystin (MC) is a cyclic heptapeptide compound which could lead to the development of hepatocellular carcinoma. However, the underlying epigenetic regulation mechanism is largely unknown. In this study, microcystin-LR (L: lysine, R: arginine, MC-LR) was used to induce the malignant transformation of human hepatocyte L02 cell line. The profile of gene expression, microRNA (miRNA) and DNA methylation were detected through high-throughput sequencing. Compared with control group, the expression of 826 genes and 187 miRNAs changed significantly in MC-LR treated group. DNA methylation sequencing analysis showed that 2592 CpG sites differentially methylated in promoter or the coding DNA sequence (CDS) of genes, while DNA methyltransferase 3 alpha ( DNMT3a ) and DNA methyltransferase 3 beta ( DNMT3b ) were dramatically up-regulated. Functional analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis showed that significantly changed mRNAs and microRNAs were mainly involved in the formation of cancer, proliferation, invasion, migration and metabolism. MiRNA-mRNA network and mRNA-mRNA network analysis showed that hsa-miR-320a, hsa-miR-331-3p, hsa-miR-26a-5p, hsa-miR-196a-5p, hsa-miR-221-3p, coiled-coil domain containing 180 ( CCDC180 ), melanoma antigen gene family member D1 ( MAGED1 ), membrane spanning 4-domains A7 ( MS4A7 ), hephaestin like 1 ( HEPHL1 ), BH3 ( Bcl-2 homology 3)-like motif containing, cell death inducer ( BLID ), matrix metallopeptidase 13 ( MMP13 ), guanylate binding protein 5 ( GBP5 ), adipogenesis regulatory factor ( ADIRF ), formin homology 2 domain containing 1 ( FHDC1 ), protein kinase CAMP-dependent type II regulatory subunit beta ( PRKAR2B ), nodium leak channel, non-selective ( NALCN ), myosin light chain kinase 3 ( MYLK3 ), epidermal growth factor receptor ( EGFR ) and zinc finger protein 704 ( ZNF704 ) were key miRNAs and genes in the malignant transformation induced by MC-LR in L02 cells. Moreover, we found that expression of MYLK3, EGFR and ZNF704 were regulated by DNA methylation and miRNAs, and these genes affected the cell cycle and cell division. Our study suggested that characteristic gene alterations regulated by DNA methylation and miRNA could play an important role in environmental MC-LR induced hepatic carcinogenesis.